2020
DOI: 10.1590/s2175-97902020000217194
|View full text |Cite
|
Sign up to set email alerts
|

Stability of hydroalcoholic extracts of two species of guaco; Mikania glomerata SPRENG. and Mikania laevigata SCHULTZ. (Asteraceae), by UHPLC-MS

Abstract: It is important to study the stability of plant extracts used as active ingredients in phytotherapic medicine, as degradation of the active principles directly affects the efficacy and safety of these products. Therefore, a stability study of the hydroalcoholic extract of the species: Mikania glomerata and Mikania laevigata was conducted in order to determine the speed of degradation and shelf life of these extracts, which are incorporated in cough syrup in Brazil. Leaves of both species were dried in an oven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…[5] This may be due to the fact that both species are creepers, grow in the same regions in Brazil and present similar foliage [6] possibly leading to misidentification of the plant material. However, studies performed by our group have repeatedly shown both species to present a different chemical composition [7,8] relentless of growth conditions. [9] Therefore, the chemical analysis of their extracts is necessary for the correct identification of these species.…”
Section: Introductionmentioning
confidence: 99%
“…[5] This may be due to the fact that both species are creepers, grow in the same regions in Brazil and present similar foliage [6] possibly leading to misidentification of the plant material. However, studies performed by our group have repeatedly shown both species to present a different chemical composition [7,8] relentless of growth conditions. [9] Therefore, the chemical analysis of their extracts is necessary for the correct identification of these species.…”
Section: Introductionmentioning
confidence: 99%